2009
DOI: 10.1242/jeb.024190
|View full text |Cite
|
Sign up to set email alerts
|

Food deprivation during photosensitive and photorefractory life-history stages affects the reproductive cycle in the migratory Red-headed Bunting(Emberiza bruniceps)

Abstract: SUMMARY In a seasonally breeding bird species, food deprivation affects reproduction. A key question is whether food shortage at any time in the year will affect reproduction even though the food supply subsequently becomes adequate. A prediction would be that a food supply that is of shorter duration than that optimally required during a life-history stage will have consequential effects on the succeeding life-history stages. Two experiments investigated this in gonadally regressed migratory Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…However, a link between the circadian and circannual rhythms is not ruled out at present as the circannual system may influence circadian rhythms (Ball and Ketterson, 2008;Mrosovsky et al, 1976). Although food availability can influence gonadal growth in seasonally breeding songbirds (Kumar et al, 2001;Budki et al, 2009), we would like to speculate based on the present results that energy turnover, enforced by the seasonality in the abundance of food resources, is not controlling the circannual rhythm underlying seasonal reproduction in the spotted munia.…”
Section: Research Articlementioning
confidence: 73%
“…However, a link between the circadian and circannual rhythms is not ruled out at present as the circannual system may influence circadian rhythms (Ball and Ketterson, 2008;Mrosovsky et al, 1976). Although food availability can influence gonadal growth in seasonally breeding songbirds (Kumar et al, 2001;Budki et al, 2009), we would like to speculate based on the present results that energy turnover, enforced by the seasonality in the abundance of food resources, is not controlling the circannual rhythm underlying seasonal reproduction in the spotted munia.…”
Section: Research Articlementioning
confidence: 73%
“…They accurately anticipate a favorable season and physiologically prepare themselves well in advance, as mistiming will have severe fitness consequences (Helm et al, 2009). Annual life-history stages begin and end at optimal times, and do not last shorter or longer than the optimal durations (Gwinner, 1996a;Gwinner, 1996b;Dawson, 2008;Budki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Also, temperature influences the food availability, which has significant effects on the photoperiodic induction of the daily and seasonal responses [26]. Budki et al [27] have reported that food deprivation during the non-breeding periods of the annual cycle affects the reproductive functions later in the year in the migratory redheaded buntings (Emberiza bruniceps). This implies that cues to which a species is exposed during a life-history stage possibly affect the events during the subsequent life-history stage [27].…”
Section: Discussionmentioning
confidence: 99%